Cartographic Visualization of Wagir Kidul Village, Pudak, Ponorogo to Optimize Accessibility and Utilization of Public Facilities - Mohammad Rozi Indrafuddin; Iis Aisyah; Risma Nur Azizah; Reza Rizqi Najafi; Azizatul Itsna; Hanang Savikhin (Community: Jurnal Hasil Penelitian dan Pengabdian Masyarakat, 2025)
This study aims to improve accessibility and the utilization of public facilities in Wagir Kidul Village through cartographic visualization. The lack of a village navigation system, such as signboards and village maps, has made it difficult for both residents and newcomers to find strategic locations. The research employed a descriptive qualitative approach using observation, documentation, and active participation of villagers and local officials. The research stages included data collection, field verification, map design, and publication through a billboard installed at the village hall. In addition, this study applied the Asset-Based Community Development (ABCD) method, which emphasizes the utilization of local assets such as community knowledge regarding village boundaries, public facility locations, and local potentials. The ABCD approach ensured that the community was not merely the recipient of benefits but also the main actor in every stage of the activity. The results show that the village map produced not only serves as an informative, accurate, and easy-to-understand navigation medium but also raises community awareness of the importance of spatial information for village development. The collaboration between students, local officials, and the community proved effective in creating practical and sustainable solutions to support village governance.